Composition and age of Jurassic diabase dikes in the Xiongcun porphyry copper–gold district, southern margin of the Lhasa terrane, Tibet, China: Petrogenesis and tectonic setting. (20th October 2017) - Lang, Xinghai; Wang, Xuhui; Tang, Juxing; Deng, Yulin; Cui, Zhiwei; Yin, Qing; Xie, Fuwei
Abstract : Diabase dikes are extensively distributed in the Xiongcun porphyry copper–gold district in the southern margin of the Lhasa terrane. Here, we report zircon U–Pb ages determined by laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) along with Hf isotopic, whole‐rock elemental, and Sr–Nd–Pb isotopic data for these diabase dikes. Zircons from one of the Xiongcun diabase dikes yielded an emplacement age of 165.3 ± 1.0 Ma. The Xiongcun diabase dikes display subalkaline features and tholeiite compositions. They are enriched in large‐ion lithophile elements (e.g., Rb, Ba, and K) and light rare earth elements and are depleted in high‐field‐strength elements (e.g., Nb, Ta, and Ti). The Xiongcun diabase dikes exhibit relatively low ratios of ( 87 Sr/ 86 Sr)i (0.70386–0.70501), ( 206 Pb/ 204 Pb)i (18.15–18.40), ( 207 Pb/ 204 P)i (15.52–15.57), and ( 208 Pb/ 204 Pb)i (38.06–39.46) and relatively high values of εNd (t) (5.85–6.92) and εHf (t) (+12.58 to +14.03). Combined with previous research results, these findings suggest that the Xiongcun diabase dikes and Early Mesozoic magmatic rocks in the southern margin of the Lhasa terrane formed in an active continental margin magmatic arc setting related to the northward subduction of the Neo‐Tethys oceanic slab; however, the possibility that the Xiongcun diabase dikes were formed in an intra‐oceanic arc setting cannot be excluded. Their parental magmas were formed by the partial melting of the depleted mantle source that was modified by fluids released from the Neo‐Tethys oceanic slab. The magmas experienced fractional crystallization of olivine and clinopyroxene and underwent limited crustal contamination during magma emplacement. The ~165 Ma Xiongcun diabase dikes, which probably originated under an extensional stress condition in a magmatic arc setting, correspond to the timing of Middle Jurassic subduction‐related porphyry copper mineralization (161–172 Ma) in the southern margin of the Lhasa terrane, likely suggesting that this episode of mineralization occurred during a period of changing stress from compression to extension.